2018
DOI: 10.1007/s13105-018-0644-y
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin B inhibition ameliorates the non-alcoholic steatohepatitis through suppressing caspase-1 activation

Abstract: Non-alcoholic fatty liver disease (NAFLD) has emerged as the most common chronic liver disease. NLRP3 inflammasome activation has been widely studied in the pathogenesis of NAFLD. Cathepsin B (CTSB) is a ubiquitous cysteine cathepsin, and the role of CTSB in the progression and development of NAFLD has received extensive concern. However, the exact roles of CTSB in the NAFLD development and NLRP3 inflammasome activation are yet to be evaluated. In the present study, we used methionine choline-deficient (MCD) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…155 For instance, cathepsin S is a cysteine protease involved in the cleavage of elastin and generation of bioactive elastin peptides. 156 Cathepsin B (CatB) is known to have a role in the production of mature IL-1β and TNFα, 157 while cathepsin K (CatK) contributes to the activation of TLR9. 158,159 The regulation of inflammatory mediators can occur at multiple levels, including transcription, mRNA translation, posttranslational modification, and mRNA degradation.…”
Section: The Initiation and Resolution Of Inflammationmentioning
confidence: 99%
“…155 For instance, cathepsin S is a cysteine protease involved in the cleavage of elastin and generation of bioactive elastin peptides. 156 Cathepsin B (CatB) is known to have a role in the production of mature IL-1β and TNFα, 157 while cathepsin K (CatK) contributes to the activation of TLR9. 158,159 The regulation of inflammatory mediators can occur at multiple levels, including transcription, mRNA translation, posttranslational modification, and mRNA degradation.…”
Section: The Initiation and Resolution Of Inflammationmentioning
confidence: 99%
“…Among them, 276 were upregulated in CI-AKI, whereas the remaining 177 were downregulated (S5 Table). These included inflammation related genes Gpnmb (glycoprotein Nmb) [43] and Cstb (cystatin B) [44], cell death related gene Gng7 (G protein subunit gamma 7) [45], as well as the renal protective gene Gstm1 (glutathione S-transferase Mu 1) [46]. These specific genes and their functions merit further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Cstb is a ubiquitous cysteine cathepsin that has been extensively studied in non-alcoholic steatohepatitis. Tang et al observed recently that Cstb might facilitate inflammation and apoptosis by promoting the expression and activity of caspase-1, as well as the secretion of IL-1β and IL-18 [44]. Ephx1 levels were observed to be significantly elevated in the rat kidney following cisplatin treatment, although the function of this protein was not further elucidated [62].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, CtsB knockout mice display preserved mitochondrial function, reduced oxidative stress and amelioration of the liver damage during NAFLD (36). CtsB inhibition using Ca074-Me has also been described to reduce hepatic inflammation and improve hepatic function in mice after MCD (Methionine-Choline-Deficient) diet feeding, by limiting NLRP3/caspase-1 activation and IL-1β and IL-18 secretion (37). Interestingly, LDL receptor-related protein-1 (LRP1) participates in cholesterol efflux via HDL secretion and plays a role in CtsD endocytosis (38).…”
Section: Cathepsins Contribution To Lipotoxicity During Nafldmentioning
confidence: 99%